MODERN SAINTS OF BHAKTI TRADITION - Chackalackal, Saju (2004)
Two polar extremes are possible between the sacred and the profane: while one stresses their individualities and, hence, their irreconcilability, the other emphasises their ultimate oneness. Although it may be unwise to pass a judgment on their ontological status, an integral approach in this regard would be to initiate a perspective of reality within which nothing can be set aside merely because a logical framework does not approve of it. In fact, all through the human history systems abound: some moderate approaches, some extreme viewpoints; some positive and some negative; some creative while others quite nihilistic. All of these were built on the intellectual contributions of those stalwarts who initiated thought provoking but hair-splitting logical analyses in order to shed light into the inner recesses of reality. Apparently, they had a reasonable number of followers who invested their time and talent to promote and propagate such systems of thought; such attempts have been identified as the leaps in the history of human thought, in the human attempt to get hold of the true nature of the ultimate reality.
Keywords: BHAKTI TRADITION